Sequential or concomitant chemotherapy in limited stage small-cell lung cancer (Swiss Medical Weekly, 2011)
PURPOSE: Chemotherapy (CT) combined with radiation therapy (RT) is the standard treatment for limited disease small-cell lung cancer (LDSCLC). Many questions including RT dose, fractionation, and sequence of RT/CT administration remain controversial. In this paper, we retrospectively assessed the outcome of patients with LDSCLC treated with radiation of at least 50 Gy. METHODS AND MATERIALS: From December 1997 to January 2006, 69 consecutive patients with LDSCLC were treated at our institutions. Treatment consisted of at least 4 cycles of CT, and 3D conformal thoracic RT. The median age was 61 years (range, 37–78 years). Sequential or concomitant CT/RT was given in 47 (68%) and 22 (32%) of the patients, respectively. The median RT dose was 60 Gy. Prophylactic cranial irradiation (PCI) was administered in 47 (68%) patients. RESULTS: With a median follow-up of 36 months (range, 6–107), 16 patients were alive without disease. The median overall survival time was 24 months, with a 3-year survival rate of 29%. The 3-year disease-free survival (DFS) and loco-regional control (LRC) rates were 23% and 60%, respectively. A better DFS was significantly associated with performance status (PS) 0 (p = 0.004), complete response to treatment (p= 0.03), and PCI group (p = 0.03). A trend towards improved overall survival (OS) was observed for patients who underwent PCI (p = 0.07). Patients treated with sequential CT/RT had a better outcome than those treated with concomitant treatment (3-year DFS rate 27% vs. 13%; p = 0.04). However, PCI was delivered more frequently for the sequential group. No significant dose-response relationship was found in terms of LRC. The multivariate analysis showed that complete response to treatment was the only significant factor for OS. CONCLUSION: Complete response to treatment was the most important factor for OS. A better DFS was significantly associated with the PCI group. We did not find a significant difference in outcome between patients receiving doses of 60 Gy or more and patients receiving 60 Gy or less.